A Study of Hadith on Women's Veils in the Perspective of Religious Moderation in Indonesia - Mardiansyah, Hamzah; Yusmita, Yusmita; Isnaini, Desi; Ulfa, Fadillah; Lubis, Mawardi (AL QUDS : Jurnal Studi Alquran dan Hadis, 2025)
The use of cadar for women in Indonesia has always been a polemic lately, often causing negative stigma. This study describes the critical analysis of hadith on the legal status of cadar for women through the approach of the concept of religious moderation in Indonesia. The research used is library research using a qualitative approach, collecting data from research sources in the form of books (hadith books), journals and other relevant readings, then analyzed using descriptive methods. The result of this study is that the cadar is a continuation of the jilbab as a covering for the awrah of believers in the Quran al-Ahzab verse 59. According to the hadith of the Prophet narrated by Abu Daud that the aurah of a believer woman is other than the face and palm and the ability to see this part of the woman before proposing. According to the principles and indicators of religious moderation, the wearing of the cadar for women believers in Indonesia does not reflect the concept of balance in religious practices and attitudes because it does not include fashion or culture of the archipelago. The conclusion of this study is that women believers do not wear a cadar in Indonesia does not mean that they do not cover their aurat, because the cadar is also related to the local culture.